A cross sectional study on infant and young child feeding practices: a keep for successful nutrition in under-five children attending rural Anganwadi centres, Mysuru - L., Divya K.; Narayana Murthy, M. R.; Nimithamohan, K.; ., Amoghashree (International Journal Of Community Medicine And Public Health, 2022)
Background: Optimal infant and young child feeding practices (IYCF) are crucial for nutritional status, growth, development, health, and ultimately the survival of children. Even with several national schemes and programs in place, India’s progress in tackling the problem of child malnutrition is slow. This study aims to estimate the prevalence of undernutrition and infant and young child feeding factors determining undernutrition among under five children in rural Mysuru. Methods: A cross sectional study was conducted among under five children who are registered in Anganwadi centres in the rural field practice area of JSS Medical College. 261 children were chosen as per population proportionate to the size sampling technique. Results: The mean age of the children was 2.8±1.2 years and 86.6% belonged to Below Poverty Line households.70.1% received breastfeeding within an hour of birth. Exclusive breastfeeding for 6 months was provided for 67.4% of the children. The prevalence of underweight, stunting, and wasting was 13.8%, 16.5%, and 5.7% respectively. The undernutrition among children was associated with the type of economic card and birth weight of the child. Conclusion: IYCF is a key area to improve child survival and promote healthy growth and development. The study calls for attention to be placed on improving and promoting participatory nutrition education to raise awareness, health literacy, and foster behavioural change communication for improved child feeding and caring practices. Additionally, sociocultural determinants of feeding practices should be addressed in the design of nutritional interventions.